Changes in prefrontal cerebral oxygenation and microvascular blood volume in hypoxia and possible association with acute mountain sickness. Issue 1 (8th August 2020) - Manferdelli, Giorgio; Marzorati, Mauro; Easton, Chris; Porcelli, Simone
Abstract : New Findings: What is the central question of this study? The role of the cerebral haemodynamic response to either normobaric or hypobaric hypoxia in people susceptible to acute mountain sickness (AMS) is still under debate. Prefrontal cortex near‐infrared spectroscopy‐derived parameters were monitored in normobaric hypoxia at rest and during moderate‐intensity exercise in AMS‐prone and non‐AMS individuals. What is the main finding and its importance? The AMS‐prone individuals did not increase microvascular blood volume and showed lower prefrontal cerebral oxygenation in normobaric hypoxia both at rest and during exercise compared with non‐AMS subjects, suggesting that these changes might underpin later development of AMS at altitude. Abstract: The aim of this study was to evaluate changes in prefrontal cerebral oxygenation and microvascular blood volume during exercise in normobaric hypoxia and to investigate possible associations with the occurrence of acute mountain sickness (AMS) at altitude. Twenty‐two healthy individuals (age, 26 ± 4 years; peak oxygen uptake, 42 ± 4 ml kg −1  min −1 ) were tested in two different conditions: normoxia (NORM) and normobaric hypoxia (fraction of inspired O2  = 0.13; HYPO). Data were collected at rest and during submaximal constant‐speed exercise. The peripheral oxyhaemoglobin saturation was measured by finger pulse oximeter. Changes in prefrontal cerebral oxygenation (ΔHbO2 ), deoxygenation (ΔHHb) and microvascular blood volume (ΔHbtot ) were obtained by near‐infrared spectroscopy. Within 2 weeks after laboratory testing, subjects rapidly ascended to 3647 m a.s.l., and AMS was evaluated using the Lake Louise scale. Eight subjects were AMS +, whereas 14 were AMS − . During NORM, near‐infrared spectroscopy variables did not change from baseline values both at rest and during exercise, with similar results in AMS + and AMS − subjects. During HYPO, ΔHHb increased to a similar extent in both groups, both at rest and during exercise. The ΔHbO2 was significantly less in AMS + compared with AMS − subjects, both at rest [−3.23 ± 5.90 versus 1.44 ± 2.14 μm, P  = 0.04, effect size (ES) = 1.1, respectively] and during exercise (−6.56 ± 5.51  versus 0.37 ± 4.36 μm,   P  < 0.01,  ES = 1.2, respectively). Total haemoglobin did not change from baseline, both at rest (−1.67 ± 9.53 μm ) and during exercise (−0.96 ± 9.12 μm ) in AMS + subjects, which was significantly different from the AMS − group (5.49 ± 3.99 μm, P  = 0.03, ES = 1.0 and 8.17 ± 7.34 μm, P  = 0.02, ES = 1.0, respectively). Individuals prone to AMS seem to be unable to increase microvascular blood volume and to maintain oxygenation at the cerebral level during exercise in acute normobaric hypoxia, suggesting that these changes might underpin later development of AMS. Abstract :